TRANSFORMATION OF SECULAR LIFE IN THE DIVINE REALITY OF THE MIDDLE AGES - Justinas Karosas (Problemos)
History of philosophy as well as that of all spiritual culture has an astonishing quality to isomorphically reveal social and practical changes of one époque or another. Therefore, medieval philosophy is naturally very closely connected with the appearance and establishment of new, i. e feudal relations, whereas the social decline of this philosophy comes hand in hand with the aforementioned crisis of these relations and the firm establishment of a new stage of civilisation. One or another state of social culture is not reali-sed in the cause of history autonomously, irrespective of people, their wishes and conseiousness. It can be realised and is realised to the extent it has become the matter of everyday life and activity of the only historians, i. e. people. Since social differentiation of people is fairy evident in the society which is based on the class hierarchy, it becomes understandable that a feudal structure of people’s life may become universal in the eyes of all member of the society only when its economic nature is ignored. Therefore, the consicientiousness of the feudal society can only be the consciousness which has no knowledge of its old original source. Based exclusively on values and not measured according to a gnoseological parameter, riligious consciousness appears to be a very important component of spiritual culture.